Immediate effects of clamping of the umbilical cord on the newborns - Hassan, Muhammad; E., Adarsh; Manjunath, Sahana; N., Shivtej; V., Archana D.; Meta, Vidhi; S., Spoorthi (International Journal of Contemporary Pediatrics, 2019)
Background: The optimal timing of cord clamping has been a controversial issue for decades. Most practitioners in developing countries clamp and cut the cord immediately after birth and this takes place during the third stage of labour. World Health Organization advises late cord clamping, however there is a debate on the optimal time for cord clamping. Delayed umbilical cord clamping appears to be beneficial for term and preterm infants. Methods: This observational study was undertaken at Rajarajeswari Medical College and Hospital, Bangalore, Karnataka, India from June 2018 to January 2019. Results: Total 100 neonates were studied of which 48 were females (48%) and 52 were males (52%). 76 babies (76%) were 3 day old in this study and 24 babies were (24%) 4 day old during the study period. 92 babies (92%) didn’t receive phototherapy in this study and 8 babies (8%) required phototherapy during the study period. No babies were polycythemic during this study period. Mean TB was 11.832 whereas mean DB was 0.5. Mean HCT was 56.332 and mean HB was 18.3002. Conclusions: Present study concluded that there are various advantages if authors practiced delayed cord clamping including higher levels of haemoglobin and haematocrit levels.